Pelatihan PELATIHAN SANTRIPRENUER MELALUI PEMANFAATAN CORELDRAW UNTUK SANTRI PONDOK MAMBA’UL HUDA KALIABU - Utami, Siwi; Dahlia, Dahlia (Jurnal AbdiMas Nusa Mandiri, 2026)
This community service activity (PkM) aims to empower students at the Mamba'ul Huda Kaliabu Islamic Boarding School through training on the use of CorelDRAW software to support the development of entrepreneurial skills known as santripreneurship. The program is motivated by the rapid advancement of information technology and digitalization, which has transformed the creative industry and increased the demand for graphic design skills. Adapting to digital transformation, particularly in producing promotional materials and visual identities, it is essential for Islamic boarding schools to develop graduates who are not only strong in religious knowledge but also competitive in the job market and technology-based entrepreneurial opportunities. This program applies an Asset-Based Community Development (ABCD) approach by identifying and utilizing local assets, including supporting facilities such as computers, laptops, projectors, internet access, alumni support with expertise in graphic design, and potential student resources. Training is conducted through interactive lectures, hands-on practice, and project-based learning, covering basic design concepts, the operation of CorelDRAW, and its application in the creation of logos, posters, and digital marketing materials. The results show a significant improvement in mastery of design tools and techniques, allowing them to produce marketable products and offer design services to the surrounding community. Collaborative support from alumni and working groups enriches the learning process. The impact of this program is reflected in the increase in creativity, confidence, and entrepreneurial motivation of students. This program shows that skills-based training with the ABCD approach effectively builds students' independence and entrepreneurial abilities in the digital economy era.